A first course in fuzzy logic, fuzzy dynamical systems, and biomathematics : theory and applications /: theory and applications. ([2016]) - Barros, Laécio Carvalho de; Bassanezi, Rodney Carlos; Lodwick, Weldon A
No abstract available